Performance and/or profit: The role of training centers (JISS) - Kawahara, T. (6. Forum on Elite Sport- IAHPSTC, Colorado Springs, USA, 9.-13. September 2009, 2009)
1997 Construction of JISS started 2000 Sport Promotion Plan 2001-2010 Sport Lottery started 2001 JISS established 2007-2008 National Training Center (Indoor Sports) 2007-2009 appoint Training Sites for non NTC Sports 2009 Additianal Budget to JISS Supplementary Budget against Financial Depression 2010 Expand NTC Accommodation to 500 beds